„Niebieskoocy” w naszej szkole – przezwyciężanie stereotypów drogą do tworzenia uczniom lepszych warunków rozwoju w klasie szkolnej - Deptuła, Maria; Borisch, Szymon (Studia Edukacyjne, 2020)
The article outlines a universal and selective prevention program aiming at weakening the risk factors – child peer rejection and the emergence and prevalence of a low skills stereotype. It is based on the cooperation of researchers with pairs of faculty members teaching in the same 4th grade: the class host and a Polish, math or a foreign language teacher. The goal of this cooperation is to create better psychosocial development conditions in interactions with teachers and peers, diminishing the sense of helplessness during Polish and math classes, the risk of stereotypes and the school– and learning-re-lated stress. The results of the seven-month cooperation will be assessed through research conducted in 18 classes randomly assigned to the trial group (9 classes) and the control group (9 classes). The pretest, after-test and the measurement of results extended for a year after the conclusion of the program will include students with the after-test covering also teachers. The socio-economic status of students’ families will be the variable controlled for.